Resistensi Antibiotik terhadap Pseudomonas aeruginosa: Literature Review - Syarif, Muhammad Reza; Kurniawaty, Evi; Rahmanisa, Soraya (CV. Jasa Sukses Abadi, 2024)
Pseudomonas aeruginosa is a gram-negative aerobic bacterium. This bacterium often causes infections in immunocompetent and immunocompromised hosts. This bacterium usually causes opportunistic infections and plays an important role in nosocomial infections. Treatment and eradication of Pseudomonas aeruginosa are very difficult because the mutation of this bacterium occurs rapidly and this bacterium is easily adaptable, causing high rates of antibiotic resistance in this bacterium. Pseudomonas aeruginosa is one of the bacteria included in the MDR ESKAPE pathogen group by WHO. This article is a literature review that examines several literatures to be made into a discussion and conclusion. Pseudomonas aeruginosa is resistant to various types of antibiotics through 3 mechanisms, namely intrinsic, acquired, and adaptive. This bacterium has minimal nutritional needs and can tolerate various temperatures, this is one of the strengthening factors for antibiotic resistance to this bacterium. WHO includes this bacterium in the critical list because of its resistance to carbapenem antibiotics. Research shows high resistance of P. aeruginosa to carbapenems, quinolones, and aztreonam. While piperacillin and tazobactam are the most effective antibiotics for this bacteria. Many classes of antibiotics have become resistant to this bacteria, so that renewal is needed in the line of treatment for infections by P. aeruginosa. Therefore, wise and rational use of antibiotics is needed so that the number of antibiotic resistance, especially to this bacteria, does not increase.